M15 Fingolimod (FTY720) Enhances Hippocampal Synaptic Plasticity and Memory in Huntington's Disease by Preventing P75NTR/TRKB Imbalance. (17th September 2014) - Miguez, A; García, G; Brito, VI; Straccia, M; Giralt, A; Ginés, S; Canals, JM; Alberch, J
Abstract : Huntington's disease (HD) is a hereditary neurodegenerative disorder characterised by motor disturbances and cognitive impairment, the latter being increasingly associated to hippocampal dysfunction. Brain derived neurotrophic factor (BDNF) is a potent neurotrophin that modulates hippocampal synaptic plasticity through its receptors TrkB and p75NTR. Fingolimod (FTY720), an agonist of sphingosine-1 phosphate receptors currently used to treat Multiple Sclerosis, has recently been shown to increase BDNF levels. We have investigated the potential beneficial effects of FTY720 in treating synaptic and memory impairments in a R6/1 HD mouse model. FTY720 delivery promoted BDNF synthesis, but not pro-BDNF cleavage, in the R6/1 hippocampus. Chronic administration of FTY720 rescued long-term memory deficits in R6/1 mice and increased the number of dendritic spines in the CA1 area of the hippocampus. R6/1 mice displayed an imbalance of p75NTR/TrkB in the hippocampus, which was prevented by FTY720 treatment through negative modulation of p75NTR. As a result, R6/1 mice showed reduced RhoA activity and higher activation of TrkB and CREB, supporting the role of FTY720 in the enhancement of synaptic plasticity. Our findings define a new mechanism for the action of FTY720 in neurodegenerative diseases, and propose this drug as a suitable candidate for treating cognitive dysfunction in HD.